Why do epidemics cause more hunger even when global food production is unaffected - Gong, Binlei; Dai, Shouhan; Wang, Shuo; Shi, Xinjie; Huang, Biao; Chen, Kevin Z. (Elsevier, 2025)
An apparent paradox is that, sufficient food is currently being produced to feed the global population, yet there has been a rising hunger in many parts of the world. An explanation that has been advanced in the literature lies in unfair food distribution within a specific region. However, empirical evidence regarding how infectious diseases influence people's food availability from a global food distribution perspective is still lacking. This paper aims to provide empirical evidence through investigating the effect of infectious diseases on hunger from the perspective of global food distribution. Using a panel data for 105 countries over the period of 1990–2016, we find that infectious diseases had no significant impact on overall global food production, but they caused more severe hunger in many countries or regions. How is that possible? The mechanism analysis shows that there was an increased flow of food from developing countries to developed countries during epidemics. Meanwhile, developing countries failed to compensate for this shortfall through either food stock or food aid, resulting in a reduced availability of food for domestic consumption. We find that epidemics caused higher domestic food prices and reduced affordability of food, which further exacerbated food insecurity and malnutrition in developing countries. To achieve the 2030 SDGs goal of Zero Hunger, it is critical to improve global food governance and enhance food distribution when facing a crisis such as epidemics.